The Impact of Unmanned Aerial Vehicle (UAV) Integration on the Effectiveness of Sea and Air Access Control in the ALKI 1 Region - Sinaga, Jepriando; Budiman, Arief; Pandjaitan, Manahan Budiarto (AGUSPATI Research Institute, 2025)
The Indonesian Archipelagic Sea Lane (ALKI) 1 is a strategic international route that is vulnerable to maritime and air security threats. The limitations of conventional surveillance systems such as patrol vessels and manned aircraft highlight the need for more effective technologies, one of which is the Unmanned Aerial Vehicle (UAV). This study aims to analyze the impact of UAV integration on the effectiveness of sea and air access control in the ALKI 1 region. The research method employed is quantitative research with 50 respondents consisting of Navy (TNI AL), Air Force (TNI AU) personnel, and related stakeholders. The independent variable is UAV integration, while the dependent variable is control effectiveness. Data were collected using a Likert-scale questionnaire and analyzed through validity and reliability tests as well as simple linear regression. The results show that all instruments are valid and reliable, with a total Cronbach’s Alpha of 0.889. Linear regression produced the equation Y = 7.842 + 0.684X, with R² = 0.572, indicating that 57.2% of the variation in control effectiveness is explained by UAV integration. The t-test (t-count 7.685 > t-table 2.011; p=0.000) and F-test (F-count 59.05 > F-table 4.04; p=0.000) confirm a significant partial and simultaneous influence. Thus, UAV integration enhances early detection, rapid response, operational efficiency, and inter-service coordination, making it a strategic instrument in safeguarding security and sovereignty along the ALKI 1 route.